Key Strategies to Reduce Waiting Time in Outpatient Pharmacy - Rahmawati, Menis; Wardhani, Viera (Fakultas Kedokteran Universitas Brawijaya, 2021)
Waiting time in the outpatient pharmacy is still a problem in hospitals. This study aimed to identify the root causes and implement solutions to reduce the waiting time at a type C hospital. This study applied a descriptive approach. The potential causes were identified using HFMEA (Healthcare Failure Mode Effect and Analysis) confirmed through an online survey on 15 staff involved in pharmacy services. Scoring and Focus Group Discussion were used to identify the priority problems and solutions. The study results revealed six causing factors of the lengthy waiting time at the outpatient pharmacy, which were doctor's schedule, absence of specific time target for each drug preparation stage, changes of the drug storage, drug stock different from the planning, incomplete standard operating procedures, and one counter for prescription collection and drug dispensing. Three solutions were implemented in six days: checking drug stock in every shift, developing an SOP, and separating the counters for prescription collection and drug dispensing. The implementation results showed a significant increase in the waiting time percentage of compounded drugs, which met the standard (≤60 minutes) from 26% to 43%. This increase was even higher for non-compounded drug waiting time (<20), from 27% to 48%. Drug stock checking, procedure standardization, and separation of service counters are the keys to reducing outpatient pharmacy waiting time.